Electrochemical Characterization of Iodide Ions Adsorption Kinetics at Bi(111) Electrode from Three-Component Ionic Liquids Mixtures. (1st January 2015) - Siimenson, Carolin; Siinor, Liis; Lust, Karmen; Lust, Enn
Abstract : The electrochemical behavior of RTIL mixtures containing 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate and 1-ethyl-3-methylimidazolium iodide were characterized by using cyclic voltammetry and electrochemical impedance spectroscopy methods. The capacitance values of the system at potentials more positive than −0.6 V (vs. Ag|AgCl| mixture of RTIL) strongly depend on the chemical nature of the anions in the mixture. Also the strong adsorption of I − at Bi(111) (well-known in aqueous and classical organic solvents) has been demonstrated in RTIL media. The capacitance values are noticeably higher for EMImOTF + EMImBF4 + 1 wt% EMImI than that for EMImOTF + 1 wt% EMImI.